Collection Development Policy Analysis: Effort to Recent The Collection of The Darussalam Gontor University Library - Desi Kholifah Fitriana; Ayuningrum, Tyas; Hidayat, Erdian; Wulansari, Ayu (Universitas Airlangga, 2024)
Background: This article discusses the analysis of collection development policies as an effort to update the existing collections at the University of Darussalam Gontor (UNIDA) library. Methods: This research method uses a descriptive qualitative approach, based on data sources through interviews, literature studies and observations, then analyzed according to the theme of the problems discussed. Purpose: The purpose of the study at the UNIDA library was to determine the consistency in implementing collection development in accordance with the collection development guidelines that were compiled and to determine the updates in the library material collection. Findings: The results of this study are an effort to determine whether the UNIDA Library has implemented a collection development policy in accordance with the guidelines and to determine the description of the updates in the library material collections at the UNIDA Library. At the UNIDA library, the available collections are not only printed but also electronic collections. In this article, the author discusses community analysis, collection policy formulation, selection stage, procurement process, weeding process. The problems faced by the UNIDA Gontor Library in implementing the collection development policy are obstacles in socialization to users and obstacles in attracting students to be more active in visiting the library. The library experiences obstacles in attracting users to be active in visiting the library. Conclusion: There are several efforts that UNIDA Gontor librarians have made to attract the interest of their students, one of which is by holding literacy classes in the library, creative prose for writing communities, but these activities have not had a big impact on students to go to the library more often Keywords: Collection; Policy; Development; Library —————————————————————————————————————————————————————- ABSTRAK Analisis Kebijakan Pengembangan Koleksi: Upaya Kemutakhiran Koleksi Perpustakaan Universitas Darussalam Gontor Latar Belakang: Artikel ini membahas tentang analisis kebijakan pengembangan koleksi sebagai upaya kemutakhiran koleksi yang ada pada perpustakaan Universitas Darussalam Gontor (UNIDA). Metode: Metode penelitian ini menggunakan pendekatan kualitatif deskriptif, berdasarkan sumber-sumber data melalui wawancara, studi literatur dan observasi kemudian dianalisis sesuai dengan tema permasalahan yang dibahas. Tujuan: Tujuan dari penelitian pada perpustakaan UNIDA untuk mengetahui konsistensi dalam melaksanakan implementasi pengembangan koleksi sesuai dengan pedoman pengembangan koleksi yang disusun dan mengetahui kemutakhiran dalam koleksi bahan pustaka. Temuan: Hasil dari penelitian ini sebagai upaya dalam mengetahui apakah Perpustakaan UNIDA sudah melaksanakan kebijakan pengembangan koleksi sesuai dengan pedoman dan untuk mengetahui gambaran mengenai kemutakhiran pada koleksi bahan pustaka yang ada di Perpustakaan UNIDA. Pada perpustakaan UNIDA koleksi yang tersedia tidak hanya tercetak melainkan ada koleksi elektronik. Dalam artikel ini penulis membahas tentang, analisis komunitas, perumusan kebijakan koleksi, tahap seleksi, proses pengadaan, proses penyiangan. Adapun masalah yang dihadapi Perpustakaan UNIDA Gontor dalam menerapkan kebijakan pengembangan koleksi adalah kendala dalam sosialisasi kepada pemustaka dan kendala dalam menarik minat pemustaka untuk lebih aktif dalam mengunjungi perpustakaan. Perpustakaan mengalami kendala dalam menarik minat mahasiswa untuk aktif dalam mengunjungi perpustakaan. Kesimpulan: Terdapat beberapa upaya yang pustakawan UNIDA Gontor lakukan untuk menarik minat mahasiswa mereka, salah satunya dengan mengadakan kelas literasi di perpustakaan, prosa kreatif untuk komunitas menulis, namun kegiatan ini belum terlalu memiliki dampak besar untuk mahasiswa agar lebih sering ke perpustakaan. Kata kunci: Koleksi; Kebijakan; Pengembangan; Perpustakaan